Understanding the Natural World through the Use of the Earth Science Kit - Dey, Tulika; Baruah, Hrishikesh; Kalita, Bhaben Chandra; Sarma, Santanu; Barthakur, Priyam; Das, Pradip Kumar; Hussain, Farooque (JOURNAL OF INDIAN EDUCATION, 2018)
School Science is an agglomeration of the three basic disciplines of science viz., physics, chemistry and biological sciences. Little attempt has been made so far in the curriculum, specifically to understand the dynamic processes of the Earth to comprehend and appreciate the wonder and awe of nature, observations of which have led to conceptualisation of the intricacies of science itself in human history. The inclusion of Earth Science in science curriculum can be a strong option to understand science holistically. The National Curriculum Framework 2005 highly recommended the use of the science kit for effective learning, through hands-on, minds-on learning approaches. In this regard, an attempt has been made to facilitate an understanding of the earth and its various processes of dynamism by developing an Earth Science Kit. This Earth Science Kit helps in understanding the many facets of nature and phenomenon of Earth. Different activities related to the Earth’s behaviour have been compiled in the kit to quench the thirst of insatiable minds.